Sustained inhibition of the NaV1.7 sodium channel by engineered dimers of the domain II binding peptide GpTx-1. Issue 21 (1st November 2015) - Murray, Justin K.; Biswas, Kaustav; Holder, J. Ryan; Zou, Anruo; Ligutti, Joseph; Liu, Dong; Poppe, Leszek; Andrews, Kristin L.; Lin, Fen-Fen; Meng, Shi-Yuan; Moyer, Bryan D.; McDonough, Stefan I.; et al.
Graphical abstract: Abstract: Many efforts are underway to develop selective inhibitors of the voltage-gated sodium channel NaV 1.7 as new analgesics. Thus far, however, in vitro selectivity has proved difficult for small molecules, and peptides generally lack appropriate pharmacokinetic properties. We previously identified the NaV 1.7 inhibitory peptide GpTx-1 from tarantula venom and optimized its potency and selectivity via structure-guided analoging. To further understand GpTx-1 binding to NaV 1.7, we have mapped the binding site to transmembrane segments 1–4 of the second pseudosubunit internal repeat (commonly referred to as Site 4) using NaV 1.5/NaV 1.7 chimeric protein constructs. We also report that select GpTx-1 amino acid residues apparently not contacting NaV 1.7 can be derivatized with a hydrophilic polymer without adversely affecting peptide potency. Homodimerization of GpTx-1 with a bifunctional polyethylene glycol (PEG) linker resulted in a compound with increased potency and a significantly reduced off-rate, demonstrating the ability to modulate the function and properties of GpTx-1 by linking to additional molecules.